Penggunaan Surat Kuasa Menjual Pada Objek Jaminan Yang Dibebani Hak Tanggungan Dalam Perjanjian Kredit Perbankan - Harry Dwicha Prayoga (Faculty of Law Universitas Islam Indonesia, 2022)
This research aims to analyze how the legal consequences of using a Power of Attorney to Sell which is used as the basis of an alternative execution of guarantees that have been bound with Mortgage for creditors (banks). Therefore, the author divides the main issue into 2 (two) parts, first, whether the use of a Power of Attorney to Sell against collateral objects that have been bound with Mortgage can be used as an alternative execution in guaranteeing certainty of the fulfillment of creditors' receivables related to debt agreements in banking credit. Second, what are the legal consequences of using a Power of Attorney to Sell against collateral objects that have been burdened with Mortgage Rights in the loan agreement for Creditors (banks)? This is a normative-qualitative research which is supported by primary legal materials and secondary legal materials. The approaches used by the author is in the form of a statutory and a conceptual approaches. The results of this study conclude that first, that the power of attorney to sell cannot be used as an alternative for execution on mortgage guarantees, since collateral that has been bound with mortgage rights will be subject to Law Number 4 of 1996 on Mortgage Rights. Second, the legal consequences arising from the use of the Power of Attorney to Sell are not binding, meaning that according to the provisions of Article 1320 of the Civil Code paragraph 4 on